Effect of Red Dragon Fruit Juice on Acrylic Resin Color - Fransiska Nuning Kusmawati; Diah Puspitasari Kusumaningrum (Ital Publication, 2019)
Background: Discoloration of denture acrylic resin base is one of the problems in appearance for patients who use them. The most common habit can cause discoloration in the denture usually associated with the patient's diet. One example is consuming red dragon fruit juice. Red dragon fruit juice contains many anthocyanin substances that can give color from colorless to purple. Furthermore, color changes indenture can also cause by the characteristic of the acrylic resin plate itself which can absorb water due to porosity. Objective: The aim of this study is to investigate the negative effects of consuming red dragon fruit juice solution on heat cured acrylic resin based plate. Methods: This type of research is laboratory experimental and the design of this research is pre-test post-test with control group design. The number of samples were 32 pieces selected using Simple Random Sampling method. The samples were divided into two groups, control (n = 16, distilled water solution) and tentative (n = 16, red dragon fruit juice solution). Color measurement using a digital spectrophotometer (VITA Easyshade). The initial color of the plate was measured before immersion into dragon fruit juice. The immersion period were 7 days to 14 days, the color of the plates was then measured after immersion. The data analysis test used was Friedman statistical test and Mann Whitney statistical test. Findings: There were significant differences in the color of the heat-cured acrylic resin plate after 7 and 14 days of immersion in distilled water solution and red dragon fruit juice solution. Novelty: Red dragon fruit juice can cause color discoloration on heat cured acrylic resin based plate.